Human Degradation: A Text-to-Film Comparison of the Human Hunts in Connell’s “The Most Dangerous Game” and Golding’s Lord of the Flies - Saravia Vargas, Juan Carlos; Saravia Vargas, José Roberto (Revista de Lenguas Modernas, 2018)
Connell’s “The Most Dangerous Game” and Golding’s Lord of the Flies, published in 1924 and 1954, respectively, rst introduced the metaphor of human hunts and they depict proto-dystopian societies where the idea of cultural progress is questioned, for individuals devolve after nding themselves subjected to the rules of a wild environment. Movie adaptations of these literary works face the dilemma of delity because, since movies are expected to generate a signi cant income, the changes res- pond to commercial considerations, which, paradoxically, affects the reception of the film. Las obras “The Most Dangerous Game”, de Connell, y Lord of the Flies, de Golding, publicadas en 1924 y 1954, respectivamente, fueron las primeras en introducir la metáfora de las cacerías humanas. En ellas aparecen so- ciedades protodistópicas, donde la idea del progreso cultural se cuestiona, ya que los individuos retroceden evolutivamente al encontrarse sujetos a las reglas de un ambiente salvaje. Las adaptaciones cinematográ cas de estos textos enfrentan el dilema de la delidad pues, dado que se espera que las películas generen un ingreso económico significativo, los cambios responden a consideraciones comerciales que, paradójicamente, afectan la recepción del filme.